Application of high-throughput fully automated air formaldehyde detection technology - Xiaoling YANG; Junhong LI; Zhiyong CHEN; Yi JIN (环境与职业医学)
BackgroundFormaldehyde is a toxic gas. Automatic iodine analyzer is a high-throughput automatic instrument for measuring water and urine iodine, but at present, there is a lack of its application in the determination for air formaldehyde. ObjectiveTo develop a high-throughput method for air formaldehyde determination with an automated iodine analyzer. MethodsThe formaldehyde in the air was collected with an atmospheric sampler, and 1.0 mL of working curve solution, standard solution, and sample solution were loaded to an automated iodine analyzer. Solution resting time and instrumental parameters, including detection wavelength, sample needle depth, and regent2 (R2) reaction time were optimized. Finally, the method was validated by precision, detection and quantification limits, and spiked recovery. Four different concentrations of standard substance solutions and 10 air samples were collected for comparison between manual measurement method and high-throughput fully automated detection method. ResultsThe final optimized conditions in this study were: 2 h and above resting time for prepared solution, and the optimal parameters of the instrument work were: detection wavelength at 660 nm, sample needle depth at 2800, and R2 reaction time at 900 s. Under the optimized conditions the linear equation of the method was optical density(D) =0.9787 × formaldehyde concentration (C) − 0.0364 and the correlation coefficient was 1.0000. The limits of detection (LOD) and quantification (LOQ) were 0.015 μg·mL−1 and 0.052 μg·mL−1 , respectively. The relative standard deviations (RSDs) of the intra-day precision experiments were 1.35% and 1.18% for the two different concentrations of standard sample solutions. The RSDs of the inter-day precision experiments were 1.82% and 1.50%, respectively. The recoveries ranged from 96.8% to 107.4%. The results produced by spectrophotometry and automated detection method in the comparison study were identical, and the measurements of selected four concentrations of standard solutions were within the uncertainty range. ConclusionThe method established in this study features small solvent dosage, fully automated high throughput, comparable sensitivity to the national standard method, high accuracy, and inter-day and intra-day precision with a recovery rate above 96%. It can provide strong technical support for the determination of air formaldehyde.